Hoax on Social Media in Alghazali’s Ethical Review - Hidayati, Nuril; Kuswanjono, Arqom; Munir, Misnal (International Journal of Psychosocial Rehabilitation, 2020)
This article is nothing but to analyze hoaxes on social media as the development of very popular media technology and the need for humans to do something digital. This research was carried out on the basis of theoretical reflection and methodology development of a new approach to the study of philosophy in the field of ethics and stressed the importance of being held fast by humans in every ever-changing era. The purpose of this paper is to find the relevance of the character’s thoughts to the problem of hoaxes on social media. The scientific renewal of this work lies in the ethical value that is universal and applies wherever and whenever, which can be understood and always actualized as a philosophical research using Islamic figures, namely al-Ghazali ethics. The results of this study are hoaxes on social media in al-Ghazali’s ethical review to be bad things that can harm others. Through al-Ghazali’s ethics, ethics can be corrected from badness (hoax) as false news into goodness to present the real news so that goodness can be felt by all without any party being harmed. Hoaxes that develop on social media are reduced and can even be prevented because of human awareness as individuals or groups on social media based on these ethics through five trainings.